2022
DOI: 10.1177/17470218221118451
|View full text |Cite
|
Sign up to set email alerts
|

Attention allocation between item and order information in short-term memory

Abstract: In immediate memory for verbal lists, recently it has been shown that participants can choose to carry out encoding that prioritizes readiness for an item test at some cost to order information or, conversely, that prioritizes readiness for an order test at a cost to item information (Guitard et al., 2021, 2022). Here we ask whether participants can control attention to items and order in a graded fashion. We examined this issue by manipulating the percentage of order or item test trials participants would rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In both studies, moreover, the costs of dual encoding were more severe for order than for items. The same was true for Guitard and Cowan (2022), who found that attention could be allocated to items and order in a fine-grained manner. Here, using a single list per trial (Guitard et al, 2022) and, unlike previous studies, we manipulate the rate of presentation, along with the attention conditions during encoding (like Guitard et al, prepare for a test of items, their order, or both).…”
Section: Rate Hypothesismentioning
confidence: 70%
See 1 more Smart Citation
“…In both studies, moreover, the costs of dual encoding were more severe for order than for items. The same was true for Guitard and Cowan (2022), who found that attention could be allocated to items and order in a fine-grained manner. Here, using a single list per trial (Guitard et al, 2022) and, unlike previous studies, we manipulate the rate of presentation, along with the attention conditions during encoding (like Guitard et al, prepare for a test of items, their order, or both).…”
Section: Rate Hypothesismentioning
confidence: 70%
“…Finally, it is theoretically possible that item information needs more allocation of attention because the item task included a cue to each item (the word fragment), which might circumvent the need for attention to some extent. Guitard and Cowan (2022) examined this possibility by conducting an experiment instead using free recall as the measure of item information, inasmuch as no cue to recall is included, and found a tradeoff with order similar to the fragment-completion case. They also found that their results with the fragment completion task were unchanged using a probability-of-knowing measure corrected for guessing.…”
Section: Discussionmentioning
confidence: 99%